Serum ascorbic acid and calcidiol status in dogs with graded periodontitis - Azargoun, R; Asri-Rezaei, S (Journal of the Hellenic Veterinary Medical Society, 2025)
The relationship between oral health and vitamins has recently attracted much attention from a dental perspective. In human dentistry, certain vitamins are well-known as the essential component in the preservation of periodontal tissue integrity and deficient conditions can predispose individuals to periodontitis. However, similar studies in veterinary medicine are scarce. The main objective of our study was an evaluation of serum levels of ascorbic acid and calcidiol in healthy dogs and those with periodontitis. Sixty healthy adult dogs were divided into 3 groups based on the depth of the periodontal pocket: periodontally healthy (pocket depth less than 2 mm), moderate periodontitis (pocket depth between 3 and 5 mm) and severe periodontitis (pocket depth more than 5 mm). Serum ascorbic acid levels in dogs with severe periodontitis were significantly lower than periodontally healthy dogs and those with moderate periodontitis (1.86±0.40, 3.93±0.84 and 3.52±0.66 respectively). Serum calcidiol levels in periodontally healthy dogs were significantly higher than groups with periodontitis (33.49±18.43, 18.08±10.05 and 13.81±6.87 respectively). The results of this research clarified that the grade of periodontitis, gingivitis and plaque indices and the age of dogs are inversely associated with the serum levels of ascorbic acid and calcidiol. It can be considered that maintaining adequate levels of serum ascorbic acid and calcidiol may be beneficial in preventing the progression of gingivitis to periodontitis and managing periodontitis in dogs.